1993
DOI: 10.1002/jnr.490350304
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 5‐hydroxytryptamine2 receptors by radioligand binding, northern blot analysis, and Ca2+ responses in rat primary astrocyte cultures

Abstract: Radioligand binding, Northern blot analysis, and changes in [Ca2+]i were used to study serotonin [5-hydroxytryptamine (5HT)] receptor subtypes in primary cultures of astrocytes from neonatal rat cerebral cortex. Radioligand binding studies revealed the presence of 5HT2, but not the 5HT1 or 5HT3 receptor subtypes. Radioligand binding was also used to show the presence of serotonin uptake sites, which had previously been shown to be present by [3H]-5HT uptake, and also alpha 1-adrenergic receptors as has previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 46 publications
3
24
1
Order By: Relevance
“…The response to 5-HT was blocked or partially inhibited by 1 µM ketanserin (Fig. 5B), which is consistent with previous studies in hippocampal primary cultures (Deecher et al, 1993). Note in Figure 5 that 50 µM Glu produced a decrease in [Ca 2ϩ ] i from the plateau of a Ca 2ϩ response to 5-HT.…”
Section: Ca 2؉ Responses In Primary Culturessupporting
confidence: 91%
See 1 more Smart Citation
“…The response to 5-HT was blocked or partially inhibited by 1 µM ketanserin (Fig. 5B), which is consistent with previous studies in hippocampal primary cultures (Deecher et al, 1993). Note in Figure 5 that 50 µM Glu produced a decrease in [Ca 2ϩ ] i from the plateau of a Ca 2ϩ response to 5-HT.…”
Section: Ca 2؉ Responses In Primary Culturessupporting
confidence: 91%
“…It required about 30 min to obtain a positive response to 10 µM 5-HT after blockade by ketanserin. This was previously reported for primary hippocampal astrocyte cultures (Deecher et al, 1993).…”
Section: Ca 2؉ Responses To Atp and 5ht In Acutely Isolated Cells Andsupporting
confidence: 57%
“…5-HT receptors have previously been demonstrated on cultured astrocytes from different brain regions (Hansson et al, 1987;Deecher et al, 1993;Whitaker-Azmitia et al, 1993). In this study, astrocytic 5-HT receptors coupled to changes in Ca 2ϩ metabolism could not be found.…”
Section: Receptor-stimulated Increases Of Intracellular Calcium In VIcontrasting
confidence: 62%
“…The explanation might be that Kir4.1 channels in the neurons might be Kir4.1/Kir5.1 heteromers (Tanemoto et al, 2000;Yang et al, 2000) that, unlike Kir4.1 monomers, do not allow anomalous gating and calcium permeability (Hartel et al, 2007 release from intracellular stores (Hartel et al, 2007). Despite an oligodendroglial expression of Kir4.1 in several regions of the CNS (Kalsi et al, 2004;Neusch et al, 2001;Poopalasundaram et al, 2000), oligodendrocytespecific features of the intracellular calcium release machinery (Kirischuk et al, 1995;Simpson et al, 1998) Astrocytes in the CNS express a variety of metabotropic receptors including those for 5-HT that increase cytoplasmic Ca 21 concentration Deecher et al, 1993;Hagberg et al, 1998;Kimelberg et al, 1997;Nilsson et al, 1991;Verkhratsky and Steinhauser, 2000). TRH and SP receptors, identified functionally and by mRNA detection, are also present (McDermott et al, 1992;Too et al, 1994).…”
Section: Oligodendrocytes and Neurons Do Notmentioning
confidence: 97%